Assessing Health Professional Education: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Assessing Health Professional Education is the summary of a workshop hosted by the Institute of Medicine's Global Forum on Innovation in Health Professional Education to explore assessment of health professional education. At the event, Forum members shared personal experiences and learned from patients, students, educators, and practicing health care and prevention professionals about the role each could play in assessing the knowledge, skills, and attitudes of all learners and educators across the education to practice continuum. The workshop focused on assessing both individuals as well as team performance. This report discusses assessment challenges and opportunities for interprofessional education, team-based care, and other forms of health professional collaborations that emphasize the health and social needs of communities.
Keywords: Education; Health and Medicine

Establishing Transdisciplinary Professionalism for Improving Health Outcomes: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Establishing Transdisciplinary Professionalism for Improving Health Outcomes is a summary of a workshop convened by the Institute of Medicine Global Forum on Innovation in Health Professional Education to explore the possibility of whether different professions can come together and whether a dialogue with society on professionalism is possible. Most of the 59 members making up the Global Forum were present at the workshop and engaged with outside participants in active dialogue around issues related to professionalism and how the different professions might work effectively together and with society in creating a social contract. The structure of the workshop involved large plenary discussions, facilitated table conversations, and small-group breakout sessions. In this way, the members - representing multiple sectors, countries, health professions, and educational associations - had numerous opportunities to share their own perspectives on transdisciplinary professionalism as well as hear the opinions of subject matter experts and the general public. Efforts to improve patient care and population health are traditional tenets of all the health professions, as is a focus on professionalism. But in a time of rapidly changing environments and evolving technologies, health professionals and those who train them are being challenged to work beyond their traditional comfort zones, often in teams. A new professionalism might be a mechanism for achieving improved health outcomes by applying a transdisciplinary professionalism throughout health care and wellness that emphasizes crossdisciplinary responsibilities and accountability. Establishing Transdisciplinary Professionalism for Improving Health Outcomes discusses how shared understanding can be integrated into education and practice, ethical implications of and barriers to transdisciplinary professionalism, and the impact of an evolving professional context on patients, students, and others working within the health care system.
Keywords: Health and Medicine

Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health discusses the connection of ecosystem services and human health. This report looks at the state of the science of the role of oceans in ensuring human health and identifies gaps and opportunities for future research. The report summarizes a workshop convened by the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine. Participants discussed coastal waters and ocean ecosystem services in the United States in an effort to understand impacts on human health. Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health focuses on key linkages by discussing the ecosystem services provided by coastal waterways and oceans that are essential for human health and well-being; examining the major stressors that affect the ability of coastal waterways and ocean systems to provide essential services; and considering key factors that can enhance the resiliency of these systems.
Keywords: Health and Medicine

Advancing Diversity in the US Industrial Science and Engineering Workforce: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Thousands of gifted individuals, including women and underrepresented minorities, remain a disproportionally small fraction of those in science, technology, engineering, and math (STEM) careers. Industry, as the largest employer category of those with STEM backgrounds, stands to benefit considerably from greater inclusion of women and underrepresented minorities in the workforce. However, nothing short of a game-changing environment must be created to harness the talent of those not fully represented in the STEM workforce. Advancing Diversity in the US Industrial Science and Engineering Workforce is the summary of a workshop held in May, 2012 by the National Academy of Engineering, focusing on the needs and challenges facing industry in particular, and it is intended to facilitate further discussion and actions to address these complex issues. The workshop provided a forum for leaders from industry, academia, and professional associations to share best practices and innovative approaches to recruiting, retaining, and advancing women and underrepresented minorities in the scientific and engineering workforce throughout the nation's industries.
Keywords: Industry and Labor; Engineering and Technology

Career Choices of Female Engineers: A Summary of a Workshop - National Research Council; National Academy of Engineering (The National Academies Press, 2014)
Despite decades of government, university, and employer efforts to close the gender gap in engineering, women make up only 11 percent of practicing engineers in the United States. What factors influence women graduates' decisions to enter the engineering workforce and either to stay in or leave the field as their careers progress? Researchers are both tapping existing data and fielding new surveys to help answer these questions. On April 24, 2013, the National Research Council Committee on Women in Science, Engineering, and Medicine held a workshop to explore emerging research and to discuss career pathways and outcomes for women who have received bachelor's degrees in engineering. Participants included academic researchers and representatives from the Department of Labor, National Science Foundation, and Census Bureau, as well as several engineering professional societies. Career Choices of Female Engineers summarizes the presentations and discussions of the workshop.
Keywords: Engineering and Technology; Policy for Science and Technology

Elder Abuse and Its Prevention: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Elder Abuse and Its Prevention is the summary of a workshop convened in April 2013 by the Institute of Medicine's Forum on Global Violence Prevention. Using an ecological framework, this workshop explored the burden of elder abuse around the world, focusing on its impacts on individuals, families, communities, and societies. Additionally, the workshop addressed occurrences and co-occurrences of different types of abuse, including physical, sexual, emotional, and financial, as well as neglect. The ultimate objective was to illuminate promising global and multisectoral evidence-based approaches to the prevention of elder maltreatment. While the workshop covered scope and prevalence and unique characteristics of abuse, the intention was to move beyond what is known about elder abuse to foster discussions about how to improve prevention, intervention, and mitigation of the victims' needs, particularly through collaborative efforts. The workshop discussions included innovative intervention models and opportunities for prevention across sectors and settings. Violence and related forms of abuse against elders is a global public health and human rights problem with far-reaching consequences, resulting in increased death, disability, and exploitation with collateral effects on well-being. Data suggest that at least 10 percent of elders in the United States are victims of elder maltreatment every year. In low- and middle-income countries, where the burden of violence is the greatest, the figure is likely even higher. In addition, elders experiencing risk factors such as diminishing cognitive function, caregiver dependence, and social isolation are more vulnerable to maltreatment and underreporting. As the world population of adults aged 65 and older continues to grow, the implications of elder maltreatment for health care, social welfare, justice, and financial systems are great. However, despite the magnitude of global elder maltreatment, it has been an underappreciated public health problem. Elder Abuse and Its Prevention discusses the prevalence and characteristics of elder abuse around the world, risk factors for abuse and potential adverse health outcomes, and contextually specific factors, such as culture and the role of the community.
Keywords: Health and Medicine